Welcome Back: Exploring Persistence Factors for Adult Learners’ Return to Basic Education in Rural Contexts - Barker, Conor; Madden, Grace; Petersen, Bonnie (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2023)
Adult education, particularly adult basic education (ABE), plays a crucial role in enabling individuals to attain secondary education or elevate their academic proficiency for post‑secondary pursuits. ABE is often the only adult education physically accessible in rural communities in Saskatchewan. ABE offers a supportive classroom environment with the necessary resources, helping learners achieve educational credentials and enhancing their personal well‑being. However, many rural ABE students face challenges that impede course completion, necessitating substantial support. This study investigates the hurdles confronting rural ABE students and the existing support mechanisms in a rural regional college system in Saskatchewan. To that end, this study explores the following questions: (1) What obstacles do ABE students in rural settings encounter? (2) What support systems are in place to foster persistence among rural ABE learners?